Spatial Influence on Form: Understanding How Space Shapes Architectural Expression - Pradhan, Aabhash; Limbu, Abhishek; Shrestha, Sajib; Shrestha, Sanjay; Bajracharya, Suchita (KEC Journal of Science and Engineering, 2026)
This research explores how space influences the way architectural form is shaped. It looks at the idea that form is not only used to define space, but can also grow out of how space is used, experienced, and understood. The study includes both theory and real examples to show how spatial needs and perceptions guide design. It also looks at how people experience these spaces after they are built. The aim is to understand how architecture can express meaning by letting space lead the design process.